Carbamazepine, triclocarban and triclosan biodegradation and the phylotypes and functional genes associated with xenobiotic degradation in four agricultural soils - Thelusmond, Jean-Rene; Strathmann, Timothy J.; Cupples, Alison M. (The Science of the total environment, 2019)
Pharmaceuticals and personal care products (PPCPs) are released into the environment due to their poor removal during wastewater treatment. Agricultural soils subject to irrigation with wastewater effluent and biosolids application are possible reservoirs for these chemicals. This study examined the impact of the pharmaceutical carbamazepine (CBZ), and the antimicrobial agents triclocarban (TCC) and triclosan (TCS) on four soil microbial communities using shotgun sequencing (HiSeq Illumina) with the overall aim of determining possible degraders as well as the functional genes related to general xenobiotic degradation. The biodegradation of CBZ and TCC was slow, with ≤50% decrease during the 80-day incubation period. In contrast, TCS biodegradation was rapid, with ~80% removal in 25 days. For each chemical, when all four soils were considered together, between three and ten phylotypes (from multiple phyla) were more abundant in the soil samples compared to the live controls. The genera of a number of previously reported CBZ, TCC or TCS degrading isolates were present; Rhodococcus (CBZ), Streptomyces (CBZ), Pseudomonas (CBZ, TCC, TCS), Sphingomonas (TCC, TCS), Methylobacillus (TCS) and Stenotrophomonas (TCS) were among the most abundant (chemical previously reported to be degraded is shown in parenthesis). From the analysis of xenobiotic degrading pathways, genes from five KEGG (Kyoto Encyclopedia of Genes and Genomes) Orthology pathways were the most dominant, including those associated with aminobenzoate, benzoate (most common), chlorocyclohexane/chlorobenzene, dioxin and nitrotoluene biodegradation. Several phylotypes including Bradyrhizobium, Mycobacterium, Rhodopseudomonas, Pseudomonas, Cupriavidus, and Streptomyces were common genera associated with these pathways. Overall, the data suggest several phylotypes are likely involved in the biodegradation of these PPCPs with Pseudomonas being an important genus. [Display omitted] •Rapid triclosan, yet slow carbamazepine & triclocarban degradation•Soils contained genera from previously reported CBZ, TCC or TCS degrading isolates.•Several functional genes were enriched in the PPCP amended samples.•Bradyrhizobium &Rhodopseudomonas were linked to xenobiotic degradation pathways.